The relationship between medical staff burnout and subjective wellbeing: the chain mediating role of psychological capital and perceived social support - Fan, Jia; Chang, Yuyang; Li, Li; Jiang, Nan; Qu, Zhifei; Zhang, Jiaxin; Li, Meihua; Liang, Bing; Qu, Danhua (Frontiers in Public Health, 2024)
Background: Medical staff play a crucial role in delivering healthcare services, especially during epidemics of infectious diseases such as coronavirus disease 2019 (COVID-19). However, there is a growing issue of burnout and low well-being among this group. While it is widely recognized that burnout has a negative impact on subjective well-being, the exact relationship between the two is not yet completely understood. The purpose of this study is to explore the chain mediating role of psychological capital and perceived social support between burnout and subjective well-being among medical staff. Methods: Using the convenient sampling method, 604 medical staff were selected for a cross-sectional study. All participants completed a self-report questionnaire that collected demographic information, as well as data from the Maslach Burnout Inventory-Human Services Survey, General Well-Being Schedule, Psychological Capital Questionnaire, and Perceived Social Support Scale. SPSS 27.0 and SPSS PROCESS macro were used for data analysis. Results: There was a significant correlation between burnout, psychological capital, perceived social support, and subjective well-being (P<0.01). Burnout not only has a direct negative impact on the subjective well-being of medical staff (effect: -0.2045; Bootstrap 95%CI: -0.2506, -0.1583), but also exerts an indirect influence on subjective well-being through three pathways: the independent mediating effect of psychological capital (effect: -0.0481; Bootstrap 95%CI: -0.0876, -0.0109), the independent mediating effect of perceived social support (effect: -0.0092; Bootstrap 95%CI: -0.0203, -0.0003), and the chained mediating effect of psychological capital and perceived social support (effect: -0.0092; Bootstrap 95%CI: -0.0183, -0.0019). Conclusions: High burnout in medical staff can impair the level of psychological capital, leading to diminished perceived social support and ultimately reduced subjective well-being. The findings of this study contribute to understanding the potential pathways between burnout and subjective well-being and provide preliminary data support for developing strategies to improve the mental health of medical staff.